Research on deployment of pooled vBRAS in cloud IP metropolitan area network - Xia GONG; Huanan CHEN; Yongqing ZHU; Shizhang YUAN; Bing YANG (Dianxin kexue)
Cloud-network integration was the main development direction of IP carrier networks.As the closest network to users, IP MAN has rich service features and it is also an important test field for network cloudification.Facing the carrier requirements of multiple access and the changes of traffic direction, IP MAN was transformed from the traditional north-south tree architecture to the Spine-Leaf architecture to meet the service requirements, such as fixed-mobile convergence and multi-cloud access scenarios.Based on the evolution of the cloud IP MAN, the deployment scheme of pooled vBRAS and key technologies were introduced, and technical reference for the large-scale commercial deployment and technology evolution of vBRAS were provided.